Wives and Wanderers in a New Guinea Highlands Society - Olive Reay, Marie (ANU Press, 2021)
Wives and Wanderers in a New Guinea Highlands Society brings to the reader anthropologist Marie Reay’s field research from the 1950s and 1960s on women’s lives in the Wahgi Valley, Central Highlands of Papua New Guinea.